2017
DOI: 10.5942/jawwa.2017.109.0027
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Microcystins in Drinking Water by ELISA and LC/MS/MS

Abstract: Enzyme‐linked immunosorbent assay (ELISA) and liquid chromatography/tandem mass spectrometry (LC/MS/MS) were compared for analyzing microcystins in water. ELISA results of microcystin‐LR spiked into raw water samples were close to the spike concentrations, but method variability was ±25%. However, ELISA‐derived microcystin‐LA concentrations were two to three times higher than the spike concentrations obtained using the kit‐provided microcystin‐LR standards, indicating the need for variant‐appropriate ELISA sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 37 publications
1
48
0
4
Order By: Relevance
“…Notwithstanding the uncertainty involved with and variable performance of the five ELISA kits in numerous studies [ 38 , 39 , 45 , 46 , 47 , 48 , 49 ], they were selected for such practical considerations as availability for the desired analytes and ease of use.…”
Section: Methodsmentioning
confidence: 99%
“…Notwithstanding the uncertainty involved with and variable performance of the five ELISA kits in numerous studies [ 38 , 39 , 45 , 46 , 47 , 48 , 49 ], they were selected for such practical considerations as availability for the desired analytes and ease of use.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, these approaches are sometimes considered too expensive to entirely remove a contaminant that occasionally occurs [68]. Ozonation, chlorination, and chloramination treatment approaches which were unable to thoroughly eliminate MCs in reagent-grade water, Colorado river water and California State Project water further generated by products [69]. The solar/chlorine process, chlorination and solar irradiation though were noted to decrease concentration and hepatotoxicity of MC-LR, complete degradation was not obtained [15].…”
Section: Treatment Approachmentioning
confidence: 99%
“…It was found that total concentrations of MCs measured by ELISA were 1.50 times higher than those measured by LC‐MS/MS, suggesting MC congeners have different sensitivities toward ELISA antibodies (Guo et al , Loftin et al ). Meanwhile, for the GLSM‐negative control, LC‐MS/MS analysis resulted in nondetects, while ELISA resulted in detections of 0.85±1.38 μg/L, which (1) suggests that the large standard deviation may be associated with variable water quality conditions when ELISA is used (i.e., the ELISA test may provide a high degree of variability when trying to compare different water supplies), and (2) is consistent with the historical abundance of demethylated MCs in GLSM, which are not measured by current LC‐MS/MS methods.…”
Section: Resultsmentioning
confidence: 99%
“…The ultimate goal of the CyanoTOX model is to predict the treatability of cyanotoxins, so it includes predictive oxidation calculations for six MCs, cylindrospermopsin (CYN), and anatoxin‐a as specific compounds based on measurements using LC‐MS/MS methods (i.e., as individual variants with their calibration curves prepared by the available standards). However, ELISA methods measure up to 100 MC variants as a group variable (i.e., as total MCs), have different sensitivities (reactivities) with different variants (Guo et al , Loftin et al ), and are more subject to interferences in the water matrix than properly conducted LC‐MS/MS methods. Nonetheless, the USEPA and other health advisories for MCs (and CYN) emphasize the use of ELISA for analysis.…”
Section: Introductionmentioning
confidence: 99%